(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2022)
An electric rickshaw (e-rickshaw) was designed and fabricated at the Federal University of Petroleum Resources Effurun, Delta State Nigeria. The E-rickshaw can be charged using the existing national electric grid and solar energy. The 58 AH lithium battery used in the E-rickshaw can be fully charged within 8 hours. It has a brushless DC motor and a motor controller of 2500W/48V. The axle of the E- rickshaw was locally fabricated in the Mechanical Engineering Workshop, Federal University of Petroleum Resources, Effurun, Delta State, Nigeria. Solidworks software was used for the computer-aided design and MATLAB-Simulink was used for the powertrain and FTP75 drive cycles of the electric rickshaw. This development is a sustainable step toward mitigating environmental pollution from fossil fuels and promoting clean energy.